GAMBARAN PENGETAHUAN MAHASISWA PRODI D3 KEPERAWATAN TENTANG BANTUAN HIDUP DASAR (BHD) DISTIKes SANTAELISABETH MEDAN TAHUN 2023 - Rusmauli; Indra Hizkia P; Frando Sitohang (Poltekkes Kemenkes Medan, 2023)
Knowledge is the result of what happens when a person senses an object, sensing occurs through the five human senses, namely, the senses (hearing, sight, smell, feeling, and touch). Basic Life Assistance (BHD) is one of the emergency relief measures that must be known by a nursing student and medical personnel, because this action is given to someone who has no awareness if not getting first aid can threaten someone's life then this action must be understood by nursing students. Before providing first aid, proper knowledge is needed, so nursing students must know. This study aims to determine the level of knowledge of D3 Nursing study program students at STIKes Santa Elisabeth Medan about Basic Life Support (BHD). This study uses a quantitative method in which data is collected by distributing questionnaires with 18 questions so as to be able to explore the knowledge of D3 Nursing students. This type of research is descriptive with a total population of 100 people. Sampling was done by total sampling technique, with a total of 100 respondents. The results show that the knowledge of D3 Nursing students at STIKes Santa Elisabeth Medan is in the good category as many as 80 respondents (80.0%) with sufficient category as many as 12 respondents (12.0%) and with less category as many as 2 respondents (2.0%) ). It was concluded that D3 Nursing study program students were in the